(untitled) (Communication & Society, 2019)
The films produced during the political transition to democracy in Spain continue to capture the interest of film analysts and historians. However, beyond the realm of fiction films, there are still many areas that have received little attention, such as the attempts to develop newsreels for cinemas once the monopoly of the Francoist No-Do newsreels had ended. This study focuses on the Noticiari de Barcelona newsreel series produced between 1977 and 1980, specifically analysing its content and its discourse. The importance of this newsreel series lies in three main factors: because it constituted one of the first steps towards the development of a Catalan film industry after the end of the dictatorship (in the midst of a debate in Spain over the need to establish autonomous film industries for each of the country’s different regions); because of the attempt it constituted to establish a local audiovisual news product in clear opposition to the No-Do newsreels; and because of its adoption of some of the themes, discursive strategies and objectives attributed to many of the independent political films of the period. All of these factors determined the content and discourse of the newsreels, and gave them an orientation that was more persuasive than strictly informative.